2018
DOI: 10.21608/adjg.2018.20023
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Dentoskeletal Changes Accompanying the Treatment of Class II Malocclusion by Advansync Appliance versus Intermaxillary Coil Spring Mechanics

Abstract: Objectives:The present study was designed to determine and compare the skeletal, dentoalveolar and soft tissue effects produced by the Advansync functional appliance and intermaxillary NiTi coil springs in the treatment of growing patients with Class II division 1 malocclusion. Subjects and methods: A sample of 19 growing patients, as evaluated by hand wrist radiographs, with age range 12-15 years was divided into two groups. Group I patients were treated with the Advansync appliance (n=10) and Group II patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 20 publications
3
10
2
Order By: Relevance
“…The increase in Co-Pt A could be due to the normal growth changes during this period of treatment or may also be due to growth of mandibular condyle in an upward and backward direction that can be stimulated by the functional orthopedic treatment. 10, 11, 15 The findings are similar in the AdvanSync2 ® group also. Schaefer et al 16 also compared the Twin Block and the Herbst appliance and did not find any significant differences between the outcomes.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The increase in Co-Pt A could be due to the normal growth changes during this period of treatment or may also be due to growth of mandibular condyle in an upward and backward direction that can be stimulated by the functional orthopedic treatment. 10, 11, 15 The findings are similar in the AdvanSync2 ® group also. Schaefer et al 16 also compared the Twin Block and the Herbst appliance and did not find any significant differences between the outcomes.…”
Section: Discussionsupporting
confidence: 66%
“…Jayachandran et al 9 reported minimal maxillary dentoalveolar effects such as decrease in U1-SN (−1.17°) and increase in U1-Aperp (0.20 mm), U6-NF (1.7 mm), and U6-Ptv (1.8 mm). However, El Mofty et al 11 reported a disparity because they found a significant retroclination of maxillary incisors (U1-SN, −5.3°) but no significant changes in maxillary molar position. The maxillary molar extrusion can be either to the distal tipping of the maxillary molar or the extrusion can be attributed to the natural tendency of the teeth to erupt occlusally and the alveolar remodeling occurring during growth.…”
Section: Maxillary Dentoalveolar Variablesmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-treatment ANB angle decreased favorably indicating a harmonious relationship of skeletal structures with soft tissues This provided a well-balanced look in the nasomaxillary complex, in accordance with reduction in facial convexity. Our results were in line the with the above-mentioned studies are comparable with a study conducted by Mofty et al,2018 who found signicant improvement in the prole of patients treated with AdvanSync2.Though the effects of the AdvanSync2 appliance are similar to other xed functional appliances (Janson et al2018, Mofty et al,2018 the greatest advantage is the ability to use the appliance from start of treatment without prior preparation of arches. This is benecial in cases with minimal residual growth, where one can utilize the remaining growth potential could be tapped quickly.…”
Section: Discussionsupporting
confidence: 92%
“…is might have brought an overlap in the ideal age of functional appliance therapy, as many studies showed that the mean increase in mandibular length is between CVMI 3 and 4. [28] is could have attributed to the significant skeletal change seen in Group B.…”
Section: Therapeutic Effects Of Advansync2 On the Mandiblementioning
confidence: 99%